APPLICATION OF GRAFTSKIN TO ACCELERATE HEALING OF ULCERS IN DIABETIC FOOT SYNDROME - M. A. Binienko; A. A. Kotslova; V. V. Davydenko; T. D. Vlasov (Вестник хирургии имени И.И. Грекова, 2016)
Diabetic foot syndrome (DFS) is one of the severe and more frequent complications of diabetes. It is characterized by occurrence of chronic purulent necrotic processes (trophic ulcers) on the foot with damage of skin, soft tissues and osteoarticular system due to pathological changes in the peripheral nervous system (diabetic neuropathy) and vascular system (diabetic angiopathy). This study aimed to evaluate the possibility of accelerating of wound healing in DFS by using the dermal equivalent (graftskin) and determine the safety of the method, factors and indications for its application. The research included 60 patients with DFS who were cured at the period from 2013 to 2016 in departments of purulent surgery of Hospital of war veterans and Municipal hospital № 14 of Saint-Petersburg. The patients were divided into 2 groups by random sampling of two comparable groups in age and sex. The patients of main group were treated by standard method and using application of dermal equivalent (DE) on the area of trophic ulcers. The patients of control group had only standard treatment. The DE showed a high efficacy in the main group of patients. The application of DE in complex treatment of patients with DFS stimulated processes of healing and accelerated the rate of epithelization. The application of DE was the most effective in patients with neuropathic form of DFS.